Hematologic and Oncologic Emergencies. Issue 1 (January 2023) - Holden, Kyle; Rao, Sheldon; White, Richard; Bangash, Salman; Madgula, Anantha Sriharsha; Schmetzer, Amy; Sangli, Swathi; Ivanova, Valentyna; Balaan, Marvin
Abstract : This article reviews both hematologic and oncologic emergencies that may be seen in the intensive care setting. Hematologic emergencies, including autoimmune hemolytic anemia, thrombotic thrombocytopenic purpura, hemolytic uremic syndrome, and disseminated intravascular coagulation, as well as oncologic emergencies including tumor lysis syndrome, superior vena cava syndrome, and cardiac tamponade secondary to metastatic disease, are discussed in detail. This review focuses on the pathophysiology, clinical features, diagnosis, and treatment of each entity.